(untitled) (Plant Tissue Culture and Biotechnology, 2026)
As a photosynthetic and single-cell microorganism, cyanobacteria is an appealing chassis that convert CO2 into high-value industrial molecules. For successful and long-term production, strategies for genetic engineering and tightly controlled promoter-gene expression are essential. Genetic tools have yet to be developed for many other potentially suitable strains for industrial applications. In this study we gave an insight into how genetic instability of Synechococcus sp. PCC 7002 can occur with the incorporation of inert (eYFP and GFP) and toxic genes (sthA) with varying constitutive and inducible promoters. The stability was investigated with both plasmid-based expression and genome integration. The tri-parental conjugation was validated after 2 weeks of incubation. Genetic instability was seen in terms of radii of the colonies rather than numbers, when repression of the toxic gene lacked e.g. with strong constitutive promoters. It was also hypothesized that Synechococcus sp. PCC 7002 did not have any repressive ability for Nickel inducible promoters, hence burden was also seen when sthA was introduced. Plant Tissue Cult. & Biotech. 35(2): 321-333, 2025 (December)